Cabinet Size and Governance in Sub-Saharan Africa - Wehner, Joachim; Mills, Linnea (World Bank, Washington, DC, 2020)
There is frequent public and media concern over the cost of bloated cabinets in many Sub-Saharan African countries. Scholarship on elite clientelism links cabinet positions with corruption and practices that undermine sound policy making. This paper presents new data on the number of ministers in African governments and shows a negative association with several measures of governance. The associations are robust in a regression framework that exploits within-country variation over time and accounts for various potential confounders. These patterns suggest that policy makers, donors, investors, and citizens should pay close attention to the number of ministers appointed to the cabinet. Although the paper cautions against simplistic policy prescriptions, a sizable increase in the number of ministers is likely bad news for governance.